2023
DOI: 10.2147/prbm.s430928
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Association Between Screen-Based Sedentary Behavior and Anxiety in Academic College Students: Mediating Role of Negative Emotions and Moderating Role of Emotion Regulation

Xili Wen,
Yujun Cai,
Kai Li
et al.

Abstract: Purpose The study aims to explore the relationship and potential mechanisms between screen time and anxiety and have a clear understanding of the role of negative emotions and emotion regulation, thus providing guidance for Chinese college students to improve mental health. Methods We conducted a questionnaire survey by selecting 1721 academic college students from 6 colleges and universities in 5 provinces in China, and the data were analyzed through the Process progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Additionally, individuals with higher educational attainment possess greater autonomy and control in their personal and professional lives, meaning they have a strong and stable sense of self-efficacy; thus, the impact of social media on them is not significant, be it positive or negative. 52 Furthermore, the purpose behind the use of social media by individuals with higher education levels may differ from other users. This segment of the population uses social media for professional, academic, or information exchange purposes, favoring a “tool-information acquisition” behavior model that prioritizes the quality over the frequency of social interactions, which manifests as an insignificant response to SMUF in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, individuals with higher educational attainment possess greater autonomy and control in their personal and professional lives, meaning they have a strong and stable sense of self-efficacy; thus, the impact of social media on them is not significant, be it positive or negative. 52 Furthermore, the purpose behind the use of social media by individuals with higher education levels may differ from other users. This segment of the population uses social media for professional, academic, or information exchange purposes, favoring a “tool-information acquisition” behavior model that prioritizes the quality over the frequency of social interactions, which manifests as an insignificant response to SMUF in the data.…”
Section: Discussionmentioning
confidence: 99%
“…The sources of negative emotions in college students are varied and complex, including academic pressure, competition, social stress, emotional issues, and financial strain ( Karyotaki et al, 2020 ). These stressors can trigger negative emotions and impair cognitive functions, such as attention, memory, and decision-making ( Gong et al, 2023 ; Wen et al, 2023 ). A national Healthy Minds Study found that over 60% of students were dealing with at least one mental health issue, such as symptoms of depression and self-injury ( Lipson et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%